PERAN TAMAN PENITIPAN ANAK BAGI WANITA PEKERJA DI PEKANBARU (STUDI KASUS DI TAMAN PENITIPAN ANAK MANSIONKIDS DAYCARE) - Mardiah, Siti; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the Mansionkids Daycare in Pekanbaru. The background of raising this issue of modernity shifts the role of mothers who should be housewives into career women whose time is more outside than at home with children. the number of working mothers and the rise of urban child care parks is interesting for writers to examine. This thesis aims to analyze whether the mother's role has been replaced by caregivers when the child is in a day care center after the parents' motivation in entrusting the child there. this research is a qualitative research with a descriptive approach. The data used are primary and secondary methods. Data collection techniques were carried out by the method of observation, interviews, and documentation all of which answered the problems of researchers regarding the role of child care parks for working women. The informants of this study were four caregivers and four mothers who left their children based on a class that was opened for children. based on the results of this study, it was found that the role of socialization and protection proved to be able to replace the role of mothers at home. It's just that the affective role is judged to be lacking because of the lack of caregivers to care for children. as for the motivation of mothers to leave their children at Mansionkids Daycare is a place that is close to work and home, works 8 hours and no one takes care of, a safe and comfortable day care park, better socialization of children, and a menu that fulfills nutrition for child.Keywords: Role, Motivation, Child Care Center